2016
DOI: 10.1097/jom.0000000000000831
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Job Satisfaction and Productivity-Related Costs

Abstract: Higher levels of job satisfaction were longitudinally related to lower total productivity-related costs and presenteeism costs, but not to lower absenteeism costs. These relationships seem to differ across job types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…Patients who struggle with IBD-related problems at work often experience increased stress levels and impaired quality of life which is why, in certain cases, accommodations to the workplace are needed in order to cope with their illness and (in)ability to work [ 4 , 6 ]. Job satisfaction is an important factor influencing work performance, and poor work satisfaction might even lead to desertion from the organization [ 7 , 8 ]. Furthermore, work-related experiences including job satisfaction and occupational balance are considered some of the most important determinants of health for people with Crohn’s disease (CD), yet they are not covered in existing patient-reported outcome (PRO) measurements used in CD [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who struggle with IBD-related problems at work often experience increased stress levels and impaired quality of life which is why, in certain cases, accommodations to the workplace are needed in order to cope with their illness and (in)ability to work [ 4 , 6 ]. Job satisfaction is an important factor influencing work performance, and poor work satisfaction might even lead to desertion from the organization [ 7 , 8 ]. Furthermore, work-related experiences including job satisfaction and occupational balance are considered some of the most important determinants of health for people with Crohn’s disease (CD), yet they are not covered in existing patient-reported outcome (PRO) measurements used in CD [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Workers who are satisfied with their job are the cornerstones of healthy and productive companies. 1 By contrast, poor job satisfaction is associated with mental-health problems such as burn-out, low self-esteem, depression and anxiety. 2 Prospective studies have shown that poor job satisfaction increases the risk of sickness absence 3 , 4 and disability pension.…”
Section: Introductionmentioning
confidence: 99%
“…For example, calendars of employees may be synchronized with continuous monitoring of stress provided by wrist tools measuring heart rate variability or skin conductance [73-75]. Simplification of questionnaires would therefore be useful and allow the introduction of other measurements such as job satisfaction [88] or work engagement [89]. Such parameters may be considered important aspects of physical, mental, and work-related well-being, as well as workplace productivity [90].…”
Section: Discussionmentioning
confidence: 99%